Qur’anic perspective on the role of education in the context of globalization: the alliance of civilization - Kayadibi, Saim; Malik, Mohammad Manzoor (2009)
The main purpose and role of education in the globalizing world should be towards developing an alliance of civilizations and ensuring its stability and sustainability. In fact, education can play a major role in instilling peaceful and mutual- understanding in the entire humanity. The moral teachings of religions lead to their common purpose, which is to build peace and maintain tranquillity among people. Religions refer to the common origin of humanity; for example, this originality is symbolized in the first created couple, Adam and Eve, and it, in principle, makes all humanity brothers and sisters. However, to make this “common origin” known to people and foster peace and harmony among them based on the teachings of religions, there appears a compelling and serious necessity of a proper dynamic of education and educating. This can be achieved through the novel and extraordinary cross- continental and intercultural communication tools, which have come along with the most striking material and ideal phenomena called globalization. However, globalization that we all are living as a reality has besides its many bright sides some dark aspects as well. Globalization is, most of the time, over simplified by its material interpretation and its essential relationship with the free market economy. Material interpretation of globalization has driven attention and focus of people to the material fact of globalization and it has thus helped ignoring the spiritual possibilities that are present in globalization but are unnoticed and unexplored. We are only aware about the economical relief and distress caused by globalization; because, this relief and distress is connected to human material happiness and because of its importance, which it receives from media and business powers. The most important aspect of globalization, which remains most of the time over looked, is the educational value which globalization carries and could carry in future. This educational quality of globalization if used and explored to its fullest can materialize an alliance of civilization based on changing human consciousness. In this paper, the role of education in the globalized world and its basic principles are investigated from the Qur’anic point of view. How the full capacity of humans can be achieved in order to discover its eternal values for harmony and coexistence. The role of education will be foregrounded on the principle of human kinship derived from Adam and Eve. How education can play a significant role in the globalized world in unifying and focusing on the common values rather than dissecting and separating. How globalization can be made the proper channel and medium of the positive education, which can help realizing a global alliance of civilizations and its requirements.